Surfactant-assisted synthesis of platinum nanoparticle catalysts for proton exchange membrane fuel cells. (19th April 2022) - Shen, Lixiao; Tu, Fengdi; Shang, Ziqi; Ma, Miao; Xia, Yunfei; Zhao, Zigang; Zhao, Lei; Wang, Zhenbo; Shao, Guangjie
Abstract: High-performance platinum nanoparticle catalysts (Pt–NPCs) remain the most widespread applied electrocatalysts for oxygen reduction reaction (ORR). Here, cetyltrimethylammonium bromide (CTAB), a surface-controlling agent, is introduced to modulate the microstructure and size of Pt nanoparticles (NPs) via a microwave-assisted heating process. The Pt-NPC assisted by 5 wt% CTAB exhibits the highest mass activity (MA) of 0.072 A mgPt −1 and specific activity (SA) of 0.077 mA cm −2, higher than those of commercial Pt/C (0.023 A mgPt −1 and 0.035 mA cm −2 ). Transmission electron microscopy (TEM) results indicate that Pt NPs are uniformly dispersed onto carbon supports with an average size of 2.39 nm. When applied in membrane electrode assembly (MEA), it exhibits the highest power density of 1.142 W cm −2, which is about 1.24 times larger than that of commercial Pt/C. Highlights: CTAB-assisted Pt–NPCs were synthesized via microwave-assisted polyol process. The CTAB directs smaller Pt nanoparticles. MEAs were prepared to investigate the practice performance of CTAB-assisted Pt–NPCs.